PENGARUH EFEK KOMUNITAS, PERSEPSI HARGA, FITUR PRODUK TERHADAP BRAND SWITCHING SMARTPHONE XIAOMI - Akbar, Muhammad Aldaraja; Rosilawati, Weny (JURNAL ILMU MANAJEMEN SABURAI, 2024)
Currently, smartphones have become a primary need for humans. Researchers want to answer the problem formulation, namely whether community effects influence smartphone brand switching, whether price perceptions influence smartphone brand switching, whether product features influence smartphone brand switching and how community influence influences smartphone perceptions. price. The data analysis method uses SEM using least squares and data processing is carried out using smart Pls3 software.The results show that the first hypothesis is supported, namely that the high community effect (x1) has a positive but not significant effect on brand switching (y). The second hypothesis is accepted, namely that the better the price perception (x2), the more positive and significant influence it will have on brand switching (y) and the product features (x3) will have a positive but not significant influence on brand switching (Y).